Associations between fucosyltransferase 3 gene polymorphisms and ankylosing spondylitis: A case-control study of an east Chinese population. - Guangming Jiang; Renfang Han; Mengya Chen; Rui Liu; Meng Wu; Xu Zhang; Yubo Ma; Yaping Yuan; Ran Wang; Zongwen Shuai; Faming Pan (PLoS ONE, 2020)
Many susceptibility genes of inflammatory bowel disease (IBD) are associated with ankylosing spondylitis (AS). Fucosyltransferase 2 (FUT2) and FUT3 genes are related to IBD. This study aimed to investigate whether these genes correlated with the susceptibility to AS. Questionnaires of 673 patients with AS, and peripheral blood specimens of the patients and 687 healthy controls were collected. FUT2 and FUT3 genes were genotyped using the SNPscan method. Frequency differences of the genes at different levels, haplotypes, and interactions were analyzed. No frequency differences were found between the cases and the controls in all the genotypes and the alleles of rs1047781, rs1800028, rs1800030, and rs812936. For rs28362459, a significant difference in allele frequencies was observed in the total participants between the groups [χ2 = 7.515, Pcorrected = 0.030; adjusted odds ratio (ORadjusted)G/T = 0.782; 95% confidence interval (CI), 0.650-0.941]. The frequencies of haplotypes TT (rs812936-rs28362459) (χ2 = 5.663, Ppermutation = 0.039) and TG (rs812936-rs28362459) (χ2 = 7.456, Ppermutation = 0.013) in the total participants, and TG (rs812936-rs28362459) in the female subgroup (χ2 = 5.624, Ppermutation = 0.047) showed significant differences between the cases and the controls. No frequency differences at the phenotypic level were found. Two-factor interactions were observed between rs28362459-TG and age, rs28362459-TG and sex, rs28362459 and rs1047781, and the Lewis and secretor status. Rs28362459-G was related to some aggravated symptoms of AS (all Pcorrected < 0.05). These findings indicated that FUT3 polymorphisms were associated with human predisposition to AS at the allele and haplotype level. Rs28362459-G might decrease the susceptibility to AS, but aggravate relevant symptoms.